Preparation and mechanical characterization of flax and glass fiber reinforced polyester hybrid composite laminate by hand lay-up method. (2018) - Meenakshi, C.M.; Krishnamoorthy, A.
Abstract: Composites are the leading materials used in industries like aerospace, shipbuilding, automobile and also in the field of renewable energy in wind turbine blade manufacturing. Amongst that fiber reinforced composites gains more importance due to its high strength and stiffness value, most of the fiber reinforced composites incorporate glass fiber as reinforcement which is a high density material and causing many environmental problems in disposal after end use. This diverts the attention of researchers towards natural fiber as a reinforcing material for structural applications which is already a highly used member in many non-structural applications. The objective of this work is hybridization of natural fiber and synthetic fiber, the natural fiber used is flax and the synthetic fiber is glass fiber along with polyester resin. The laminates are prepared with different volume of flax and glass fiber and their mechanical properties like tensile strength, impact strength, flexural strength and water absorption nature are tested. The tests are carried out on standard ASTM sized samples the results show that the hybrid composite is showing equally good performance to conventional glass fiber composite and overall better performance than the mono natural Fiber composite.